Structure, phase states and change of magnetic properties at recrystallization of thin-film Ni laser condensates - Bagmut, A.G.; Shipkova, I.G.; Zhuchkov, V.A. (Functional Materials, 2009)
The influence of a substrate temperature and of oxygen pressure in the evaporation chamber on the structure and phase state of nickel laser condensates has been studied by electron microscopy. The regularities of structure-phase transformations in the films and changes of magnetic properties after annealing have been investigated. It is established that a wide spectrum of thin-film states can be provided by varying the oxygen pressure in the evaporation chamber and the substrate temperature during nickel condensation. Amorphous Ni films are formed as well those with metastable HCP lattice ( phase), with stable GCC lattice ( phase), and NiO films with FCC structure. The effective activation energy value for the processes controlling the formation of  phase of Ni grains makes about 0.26 eV /atom. Annealing of amorphous films initiates their crystallization with formation of disordered precipitates of  phase of nickel. Annealing of Ni films with metastable HCP lattice initiates the HCP -> FCC polymorphic transformation accompanied by sharp increase of grain size and changes in its magnetic properties. The annealed films get a magnetic moment and hysteresis is observed at magnetization reversal. Проведено електронно-мікроскопічне дослідження впливу температури підкладки та тиску кисню у випарній камері на структуру та фазовий склад лазерних конденсатів нікелю. Вивчено закономірності структурно-фазових трансформацій та зміни магнітних властивостей плівок після відпалу. Установлено, що варіювання тиском кисню у випарній камері й температурою підкладки у процесі конденсації нікелю забезпечують широкий спектр тонкоплівкових станів. Формуються аморфні плівки Ni, плівки Ni з метастабільною ГПУ решіткою ( фаза), плівки Ni зі стабільною ГЦК граткою ( фаза) і плівки оксиду Ni зі структурою ГЦК. Ефективне значення енергії активації процесів, що контролюють утворення зерен  фази Ni, становить - 0,26 еВ/атом. Відпал аморфних плівок ініціює їхню кристалізацію з утворенням розорієнтованих виділень  фази нікелю. Відпал плівок Ni з метастабільною ГПУ граткою ініціює поліморфне перетворення ГПУ -> ГЦК, що супроводжується різким збільшенням розміру зерен і зміною магнітних характеристик плівки. У результаті відпалу плівки набувають магнітного моменту, а при перемагнічуванні має місце гістерезис. Проведено электронно-микроскопическое исследование влияния температуры подложки и давления кислорода в испарительной камере на структуру и фазовый состав лазерных конденсатов никеля. Изучены закономерности структурно-фазовых трансформаций и изменение магнитных свойств пленок после отжига. Установлено, что варьированием давления кислорода в испарительной камере и температуры подложки в процессе конденсации никеля можно обеспечить формирование широкого спектра тонкопленочных состояний. Конденсируются аморфные пленки Ni, пленки Ni с метастабильной ГПУ решеткой ( фаза), пленки Ni со стабильной ГЦК решеткой ( фаза) и пленки оксида NiO со структурой ГЦК. Эффективное значение энергии активации процессов, контролирующих образование зерен  фазы Ni, составляет - 0,26 эВ/атом. Отжиг аморфных пленок инициирует их кристаллизацию с образованием разориентированных выделений  фазы никеля. Отжиг пленок Ni с метастабильной ГПУ решеткой инициирует полиморфное превращение ГПУ -> ГЦК, которое сопровождается резким увеличением размера зерен и изменением магнитных характеристик пленки. В результате отжига пленки приобретают магнитный момент, а при перемагничивании имеет место гистерезис.